Doping in cycling. Interdisciplinary perspectives (Ethics and sport, 2018)
Doping in Cycling: Interdisciplinary Perspectives provides an up-to-date overview of the knowledge about doping and anti-doping in the sport that has dominated doping headlines for at least two decades. It critically addresses overarching questions related to doping and anti-doping, and topical issues being raised in the agenda of policy-makers at the global level.